Relationships between University graduates' marks and their labour outcomes. (European Journal of Education and Psychology, 2009)
There are many different factors involved on university graduates’ decision making about their own careers after graduation, being university grades a main element to be considered. University grades’ hypothetical role as mediator on this process and relationships between this variable, invested time to obtain a job and involvement on postgraduate programs are analyzed on this study. Researched population consists of 15.360 graduates who finished their degrees between 2002 and 2007 in La Laguna’s University. Data shows graduates who are involved on postgraduate programs and those who invest more time to obtain a job usually had better grades. However, results are different on some health degrees such as Medicine or Physiotherapy, probably because Health Services have their own recruitment procedures.Key words: Labour outcomes, european space for higher education.